Influence of Condensed and Hydrolysable Tannins on the Bacterial Community, Protein Degradation, and Fermentation Quality of Alfalfa Silage - Wencan Ke; Huan Zhang; Shengnan Li; Yanlin Xue; Yan Wang; Wencheng Dong; Yimin Cai; Guijie Zhang (Animals, 2022)
This study evaluated the effects of hydrolysable tannin (HT) and condensed tannin (CT) on the bacterial community, fermentation quality, and proteolysis of alfalfa silage. Alfalfa was wilted to a dry matter (DM) of 35% fresh weight and ensiled with or without 4% HT or 4% CT. The application rates of tannins were based on fresh weight, and each treatment was ensiled in triplicate. After 60 d of fermentation, the CT-treated group had lower concentrations of ammonia nitrogen (NH3-N) and free amino acid nitrogen (AA-N), but greater lactic acid concentration, than those in the control and HT-treated silage (p < 0.05). Compared to the control group, the application of tannins increased the abundance of Pseudomonas (negatively correlated with aminopeptidases activity), and decreased the abundance of Pediococcus—which was positively correlated with aminopeptidases activity—and the concentrations of non-protein nitrogen (NPN), NH3-N, and AA-N. The application of HT decreased the abundance of Lactobacillus and increased the abundances of Enterococcus, while the opposite results were observed in the CT-treated group. The application of HT and CT reduced the proteolysis in treated silages, but the two were different in terms of their mechanism and their effects on the bacterial communities of the alfalfa silage.